Effect of population density on diet composition and dietary niche breadth of guanaco (Lama guanicoe, Müller 1776) in northeastern Patagonian steppes - Rodriguez, María Victoria; Marino, Andrea Ivana; Borrelli, Laura Beatriz; Bay Gavuzzo, Alhue; Pazos, Gustavo Enrique (Elsevier, 2019)
The optimal foraging theory postulates that as animal population density increases, the progressive decline in preferred forage availability results in changes in diet composition and widening of dietary niche breadth. For sedentary guanaco populations, some authors proposed a mechanism of population density limitation below the environmental carrying capacity, mediated through territoriality. Under the optimal foraging theory, increased density would lead to changes in guanaco diet selectivity and composition. Conversely, under the self-regulation hypothesis, guanacos would not affect preferred forage availability and no differences in guanaco diet would be expected. We tested these contrasting hypotheses by assessing both the differences in the proportion of grasses and shrubs present in guanaco diet and dietary niche breadth at three contrasting densities in northeastern Patagonian steppes. We did not find guanaco density effects on preferred forage availability, grass-shrub proportions in the diet and diet selectivity. Guanacos showed a mixed diet composed by plant species of both high and low nutritional quality independently of population density. The lack of changes in diet composition suggests that guanacos did not perceive a restriction in forage availability in terms of either biomass or nutritional content, regardless the observed increase in population density.